STERILITY OF MALE AEDES AEGYPTI POST 3-RAY STERILIZATION - B.Ernawan; H.I.Sasmita andA.A.Parikesit CenterforIsotopesandRadiationApplication-NationalNuclearEnergyAgency(CIRA-Batan).Jl.LebakBulusRaya (Journal of Animal and Plant Sciences, 2018)
Aedes aegypti(Ae. aegypti),avectorofdenguehemorrhagicfever(DHF),populationcontrolwasdevelopedusingthe sterile insect technique (SIT). Sterilization process was conducted using 3-ray sterilization. To support the SIT st th application,thesterilityofmale Ae. aegyptionthe1-5 dayspoststerilizationwerestudied.Thefirststepofthis researchwasthesterilizationprocessofmale Ae. aegyptiwith70Gyof3-raysterilization.Then,thesterilemaleAe. st nd rd th th aegyptimosquitoesonthe1;2 ;3 ;4 and5 daysafterthesterilizationprocessrespectivelywerecompetedwithun- irradiatedmalestomatewithun-irradiatedfemales.Thenumberofeggsthatwereproducedwasincubatedtodetermine thefertilityofsterilemale Ae. aegypti.Theresultshowedthattheaveragenumberofeggsproducedfrommating st th combinationofsterilemale Ae. aegyptimosquitoesonthe1-5 dayspoststerilization,un-irradiatedfemalesandun- irradiatedmaleswas1,135;1,118;1,243,1,372and1,326.Theaveragepercentagenumberofeggsthatdidnothatch intolarvaewas97.69%;97.87%;90.92%,96.20%,and86.91%.Byanalysisofvariance(ANOVA),thenumberand percentageoftheunhatchedeggswerenotsignificantlydifferentatthelevelconfidentof95%.Theresearchshowedthat st th thematingabilityandsterilityofsterilemale Ae. aegyptionthe1-5 dayspost3-raysterilizationshownosignificant difference. DENVvectorarecrucial.Itshouldbenotedthatfemale
Keywords: Sterileinsecttechnique(SIT); sterility; Aedes aegypti; 3-raysterilization.